Pancasila dalam Dinamika Politik Identitas di Masyarakat Dayak - Lafdy, Valentino (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
The research discussed in this scholarly work focuses on identity politics that has plagued the Indonesian nation due to abuses. The politics of abuse must be countered with the foundations contained in Pancasila, so that identity politics does not occur. For this, the method used is a quantitative research method. With this method, the author can describe Pancasila and identity politics with the data obtained, so that the reader can understand and reflect that unity is very important for this country. Therefore, this study will produce an outcome, which is to reverse identity politics into unity in social diversity or commonly known as tolerance to reconcile Indonesia and promote the prosperity of the community. advanced and growing Dayak coin. In West Kalimantan, the Dayak people were the first to seize the opportunity to openly organize along ethnic lines and pursue ethnic political goals. Immediately after the fall of the New Order, the Dayak people took to the streets demanding the appointment of Dayak police chiefs in two districts. This chapter examines the role of the Reformation, or post-New Order reform period, in Dayak politics and how Dayak politics has evolved since then. To understand the early development of Dayak politics in West Kalimantan, we will first look at how West Kalimantan experienced political transitions and intense Dayak political lobbying, including the government and other reactions from the large ethnic group, the Malays.